2010
DOI: 10.1071/mf08326
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of periphyton are determined by cascading trophic relationships in two neotropical streams

Abstract: Indirect foodweb interactions often determine the dynamics of aquatic ecosystems. Predators may reduce the activity of herbivores, which, in turn, may cause basal resources to increase. We studied the patterns of distribution of periphyton (organic and inorganic mass and chlorophyll) on rocks in pools in two Atlantic rainforest coastal streams that varied with respect to the presence or absence of fish. A steep waterfall apparently prevented most fish species from colonising the upper parts of one stream; the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 35 publications
2
25
0
2
Order By: Relevance
“…However, some tropical fish have been found to be vitally important in increasing periphyton growth rates (Pringle & Hamazaki, 1997;Moulton et al, 2010), which may explain high levels of ambient periphyton in below-waterfall pools and low periphyton growth rates in the above-waterfall pool of Apan Threelan (0.04 g m -2 days -1 ) where no fish were present. Overall abundance of ambient periphyton was correlated with the occurrence of fish.…”
Section: Ecosystem Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some tropical fish have been found to be vitally important in increasing periphyton growth rates (Pringle & Hamazaki, 1997;Moulton et al, 2010), which may explain high levels of ambient periphyton in below-waterfall pools and low periphyton growth rates in the above-waterfall pool of Apan Threelan (0.04 g m -2 days -1 ) where no fish were present. Overall abundance of ambient periphyton was correlated with the occurrence of fish.…”
Section: Ecosystem Functionsmentioning
confidence: 99%
“…The different community structures of fish and shrimp above and below waterfalls can influence a range of ecosystem functions including organic matter decomposition and periphyton growth (Greathouse & Pringle, 2006;Moulton et al, 2010;Ho & Dudgeon, 2016). Below waterfalls, high numbers of fish can play an important role in controlling periphyton growth by clearing rock surfaces after frequent tropical flood events (Pringle & Hamazaki, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Considering this, we believe that fish can have a strong negative effect on shrimps that are excluded even when suitable abiotic conditions exist. This negative fish effect was reported for other rainforest streams (Moulton et al, 2013) and in our sites it seems to affect especially M. potiuna which is smaller, weaker and less aggressive than M. olfersii (Silveira, 1997;Moulton and Silveira, 1998). The distribution M. potiuna appears to be negatively affected by M. olfersii (Moulton and Silveira, 1998), but since M. olfersii was relatively rare in the studied sites, it was probably not a strong factor in restricting M. potiuna to smaller streams.…”
Section: Discussionmentioning
confidence: 70%
“…We collected no Atyidae shrimps in the traps and did not observe them. Potimirim brasiliana is very common in small, coastal, streams, especially in places without fish (Moulton et al, 2013). It is amphidromous, and because it is much smaller than other amphidromous Macrobrachium species, it possibly does not have as strong ability to inhabit upstream locations compared to these species.…”
Section: Discussionmentioning
confidence: 99%
“…6). Previous research in these streams showed a strong indirect relationship of sites with fish and the density of periphyton (Moulton et al, 2010). Apparently, the presence of fish had an inhibiting effect on grazing shrimp (Potimirim), such that sites with fish had greater density of periphyton.…”
Section: Shredders Accumulated Leaves and Breakdown Ratesmentioning
confidence: 99%